Nonmagnetic band gap at the Dirac point of the magnetic topological insulator (Bi1−xMnx)2Se3 - J. Sánchez-Barriga (Nature Portfolio, 2016)
Doping a topological insulator with magnetic impurities is expected to induce ferromagnetism and open a band gap in its surface states. Here, the authors study Mn-doped Bi2Se3, finding a mechanism for band gap opening in topologically-protected surface states which is not of magnetic origin.